A bcp for photoelectrode-modified perovskite photovoltaic device and a preparation method thereof

CN116669510BActive Publication Date: 2026-10-09HENAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310725706.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2026-10-09
Estimated Expiration
2043-06-19

AI Technical Summary

Benefits of technology

[0014] This invention reduces interface defects by modifying the ITO surface with BCP. Simultaneously, BCP acts as a hole-blocking layer, preventing hole transport and facilitating electron conduction. Furthermore, the SnO2 film readily exhibits nanopores, leading to direct contact between BCP and perovskite. This strong interaction allows for the regulation of perovskite crystallization, achieving directional growth and resulting in perovskite thin films suitable for fabricating high-performance photovoltaic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116669510B_ABST
    Figure CN116669510B_ABST
Patent Text Reader

Abstract

The application discloses a kind of BCP for photoelectrode modification perovskite photovoltaic device and preparation method thereof, comprising the following steps: preparation BCP solution and spin coating on ITO substrate;SnO2 solution is prepared and spin coating on BCP;PbI2 solution is prepared and spin coating on SnO2;Preparation of mixed solution of ammonium halide salt and spin coating on PbI2;Preparation of PEAI solution and spin coating on halide ammonium salt;Preparation and spin coating spiro-OMeTAD on PEAI, to obtain ITO / BCP / SnO2 / Perovskite / PEAI / spiro-OMeTAD sample;Electrode evaporation.The application is processed by BCP to ITO substrate, which is conducive to the blocking of hole and the transmission of electron;Secondly, BCP carries out interface modification to SnO2 electron transport layer, reduces interface defect;In addition, a small amount of BCP is contacted with perovskite interface, promotes the growth of perovskite grain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials chemistry, specifically relating to a perovskite photovoltaic device modified with BCP for photoelectrode and its preparation method. Background Technology

[0002] Fossil fuels are the primary energy source in the modern era. However, the burning of fossil fuels has caused irreversible environmental damage, and since fossil fuels are non-renewable, humanity has had to find a clean and renewable energy source to replace traditional fossil fuels. As a result, solar energy, wind energy, and other energy sources have emerged. Against this backdrop, the efficient conversion of solar energy into electrical energy has become urgent. In addition, compared with traditional silicon-based solar cells, perovskite photovoltaic devices have the advantages of simple fabrication process and high efficiency. However, during the fabrication process of perovskite photovoltaic devices, problems such as interface defects and non-radiative reloading are easily encountered. The addition of BCP modifies the ITO interface, reducing defects. At the same time, it acts as a hole blocking layer material, blocking hole transmission. Furthermore, after adding BCP modification, the crystallinity of the device on the (111) crystal plane is better (Science, 2023, 379(6628):173-178), and the stability is improved, providing a new method for fabricating more efficient and stable perovskite photovoltaic devices. Summary of the Invention

[0003] The purpose of this invention is to provide a perovskite photovoltaic device with BCP for photoelectrode modification and a method for its fabrication. This invention improves the interface defect problem and charge accumulation recombination problem in the electron transport layer.

[0004] By spin-coating BCP onto the ITO / SnO2 interface, the bottom of SnO2 is modified, which is beneficial for electron transport and hole blocking. In addition, the SnO2 layer is prepared by nano-SnO2 dispersion. This layer has nano-voids. When the perovskite layer is made, some perovskite solution will contact the bottom ITO / BCP through the voids. After film formation, BCP is in direct contact with perovskite grains. The strong interaction between them is beneficial to promote the directional growth of perovskite grains, that is, growth along the (111) plane, thereby improving the photoelectric conversion efficiency and stability of the device. Thus, a high-efficiency and stable perovskite photovoltaic device is prepared.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for fabricating a perovskite photovoltaic device modified with BCP (biofilm polymerase chain) as a photoelectrode includes the following steps: (1) The ITO (indium tin oxide) substrate was cleaned by ultrasonic cleaning with glass cleaner, acetone and isopropanol respectively, then dried with nitrogen, and then treated with ultraviolet ozone. (2) Prepare and spin-coat BCP solution, and obtain ITO / BCP sample after ultraviolet ozone treatment; (3) Prepare SnO2 solution, spin-coat SnO2 solution on ITO / BCP substrate, and then obtain ITO / BCP / SnO2 sample after annealing and ultraviolet ozone treatment; (4) Prepare PbI2 solution, spin-coat PbI2 solution onto the sample obtained in step (3) in a nitrogen glove box, and anneal to obtain ITO / BCP / SnO2 / PbI2 sample; (5) The ITO / BCP / SnO2 / PbI2 sample obtained in step (4) was spin-coated with a mixed solution of ammonium halide salts under nitrogen protection and annealed to obtain the ITO / BCP / SnO2 / perovskite sample. (6) Prepare PEAI solution and spin-coat PEAI solution onto the ITO / BCP / SnO2 / perovskite sample obtained in step (5) to obtain ITO / BCP / SnO2 / perovskite / PEAI sample; (7) Spin-coat spiro-OMeTAD onto the ITO / BCP / SnO2 / perovskite / PEAI sample obtained in step (6) to obtain a sample with an ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD structure.

[0006] (8) Gold electrodes are deposited on the sample with the ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD structure obtained in step (7) to obtain a perovskite photovoltaic device with the ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au structure.

[0007] Preferably, in step (2), the BCP solution is prepared as follows: BCP powder is added to isopropanol and stirred for 5-7 hours to prepare a 0.5 mg / ml BCP solution. The spin-coating amount of the BCP solution is 20-30 μL / cm. 2 .

[0008] Preferably, in step (3), the SnO2 preparation process is as follows: dilute the SnO2 colloidal dispersion (15wt%) with deionized water to 10wt%, stir for 20min to obtain SnO2 solution; in step (3), annealing refers to annealing at 100℃ for 5 minutes and then annealing at 150℃ for 10 minutes.

[0009] In steps (1), (2) and (3), the wavelength of the ultraviolet light during ultraviolet ozone treatment is 180~190nm, and the temperature of the treatment process is 40~45℃.

[0010] Preferably, in step (4), the specific preparation process of the PbI2 solution is as follows: PbI2 is dissolved in a mixed solution of DMF and DMSO with a volume ratio of 9:1, and stirred for 10-15 hours to obtain a PbI2 solution of 1.5 mmol / mL; annealing in step (4) refers to annealing at 70°C for 1 minute. The spin-coating amount of the PbI2 solution is 7-8 μL / cm. 2 .

[0011] Preferably, in step (5), the specific preparation process of the ammonium halide salt mixed solution is as follows: FAI, MAI, and MACl are added to isopropanol to prepare an ammonium halide salt mixed solution with a concentration of 105.36 mg / mL; in step (5), annealing refers to annealing at 150°C for 15 minutes in air with a humidity of 30%-40%. The spin-coating amount of the ammonium halide salt mixed solution is 20~30 μL / cm. 2 .

[0012] Preferably, in step (6), the preparation process of PEAI is as follows: PEAI is dissolved in isopropanol to prepare a PEAI solution; the spin-coating amount of the PEAI solution is 15~25 μL / cm. 2 .

[0013] Preferably, in step (7), the preparation process of spiro-OMeTAD is as follows: take 72.5 mg of spiro-OMeTAD, add 1 ml of chlorobenzene, 18 μl of lithium bis(trifluoromethanesulfonyl)imide acetonitrile solution (520 mg / mL), 28.5 μl of 4-tert-butylpyridine, and stir for 12 hours; The BCP prepared by the above method is used for perovskite photovoltaic devices modified with photoelectrodes. Specifically, the SnO2 layer has a thickness of 40 nm, the perovskite layer has a thickness of about 650 nm, the spiro-OMeTAD layer has a thickness of about 160 nm, and the gold layer has a thickness of 80 nm.

[0014] This invention reduces interface defects by modifying the ITO surface with BCP. Simultaneously, BCP acts as a hole-blocking layer, preventing hole transport and facilitating electron conduction. Furthermore, the SnO2 film readily exhibits nanopores, leading to direct contact between BCP and perovskite. This strong interaction allows for the regulation of perovskite crystallization, achieving directional growth and resulting in perovskite thin films suitable for fabricating high-performance photovoltaic devices. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the battery structure of the present invention; Figure 2A comparison of current density-voltage (JV) curves for photovoltaic devices with ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au and ITO / SnO2 / perovskite / PEAI / Spiro-OMeTAD / Au structures; Figure 3 Cross-sectional scanning electron microscope (SEM) image of ITO / BCP / SnO2 / perovskite; Figure 4 X-ray diffraction (XRD) patterns of perovskite thin films with two structures: ITO / BCP / SnO2 / perovskite and ITO / SnO2 / perovskite. Figure 5 For photovoltaic devices with two structures—unencapsulated ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au and ITO / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au—the following were evaluated: (a) long-term stability in a nitrogen environment; (b) thermal stability under continuous heating at 85°C in a nitrogen environment; and (c) continuous illumination (100 mW / cm²) in a nitrogen environment. -2 Light stability. Detailed Implementation

[0016] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited thereto.

[0017] Table 1. Description of materials used in the experiment Example 1 A method for fabricating perovskite photovoltaic devices modified with BCP (biofilm polymerase chain) as a photoelectrode, the process is as follows: (1) Prepare BCP solution in nitrogen glove box: Take BCP powder, add it to isopropanol, stir for 6 hours to prepare a 0.5 mg / mL BCP solution; (2) Prepare SnO2 solution: dilute SnO2 solution (15wt%) with deionized water at a volume ratio of 2:1, stir for 30 minutes after dilution to obtain 10wt% SnO2 solution; (3) Prepare PbI2 solution in nitrogen glove box. Take 1.5 mmol of PbI2 powder, dissolve it in 1 mL of a mixed solution of DMF and DMSO with a volume ratio of 9:1, stir for 12 hours, and finally obtain PbI2 solution. (4) Prepare a mixed solution of ammonium halide salts by dissolving 90 mg (0.52 mmol) FAI, 6.36 mg (0.04 mmol) MAI, and 9 mg (0.13 mmol) MACl in 1 mL of isopropanol and stirring for 12 hours. (5) Prepare PEAI solution by using isopropanol as solvent to prepare a 5 mg / ml PEAI solution; (6) Prepare spiro-OMeTAD solution in a nitrogen glove box. Take 72.5 mg of spiro-OMeTAD, add 1 ml of chlorobenzene to it, stir for one hour, and then add 28.5 μl of 4-tert-butylpyridine and 18 μl of lithium bis(trifluoromethanesulfonyl) acetonitrile solution (520 mg Li-TFSI dissolved in 1 mL of acetonitrile) to prepare spiro-OMeTAD solution.

[0018] (7) Take 2×2 cm 2 The ITO glass substrate was ultrasonically treated with glass cleaner, deionized water, acetone and isopropanol for 45 minutes each, then dried with nitrogen, and then treated with ultraviolet ozone cleaner that generates 185nm ultraviolet light for 20 minutes at a temperature of 40~45℃. (8) Spin-coat 100 μL of BCP solution onto a conductive glass substrate with ITO at a speed of 4500 rpm for 20 seconds, and then treat it with UV ozone in a UV cleaner that generates 185 nm UV light for 20 minutes at a temperature of 40~45℃. (9) The prepared SnO2 solution was filtered through a 0.22 mm water filter head, and then 100 μl of the solution was spin-coated at a speed of 5500 rpm for 10 seconds. After spin-coating, the solution was annealed at 100℃ for 5 minutes and then at 150℃ for 10 minutes. After that, it was treated with ultraviolet light in an ultraviolet ozone cleaner that generates 185 nm ultraviolet light for 60 minutes. The temperature of the treatment process was 40~45℃. The thickness of the SnO2 film obtained was about 40 nm. (10) After filtering the PbI2 solution with a 0.22 mm organic filter head, take 30 μl of the solution and spin-coat it onto the ITO / BCP / SnO2 sample. The rotation speed is 1500 rpm and the time is 1 minute. Anneal at 70℃ for 1 minute. After the sample is cooled to room temperature, the ITO / BCP / SnO2 / PbI2 sample is obtained. (11) The ammonium halide salt mixed solution was filtered using a 0.22 mm organic filter head. 100 μl of the solution was spin-coated onto the ITO / BCP / SnO2 / PbI2 sample at a speed of 2000 rpm for 30 seconds. The sample was then transferred to air with a humidity of 30%-40% for annealing at a temperature of 150°C for 15 minutes. After cooling to room temperature, the ITO / BCP / SnO2 / perovskite sample was obtained. The thickness of the perovskite film obtained was approximately 650 nm. (12) Transfer the ITO / BCP / SnO2 / perovskite sample back to the glove box, take 80 μl of PEAI solution and spin coat it onto the ITO / BCP / SnO2 / perovskite sample at a speed of 5000 rpm for 30 seconds to obtain the ITO / BCP / SnO2 / perovskite / PEAI sample. (13) Filter the spiro-OMeTAD solution using a 0.22 mm organic filter head, take 20 μl of the solution and spin-coat it onto ITO / BCP / SnO2 / perovskite / PEAI at a speed of 4500 rpm for 20 seconds. The thickness of the spiro-OMeTAD film obtained by spin-coating is about 160 nm. (14) Finally, gold electrodes were deposited on the obtained sample using a vacuum evaporation instrument. The thickness of the gold was approximately 80 nm, and the area of ​​the device was 4 mm. 2 Through the above steps, a photovoltaic device with the structure ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au (labeled as: optimized device) is obtained, as shown in the figure. Figure 1 As shown.

[0019] The preparation process of the reference device ITO / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au for comparison is the same as in Example 1, except that steps (1) and (8) are omitted.

[0020] Figure 2 The graph compares the current-voltage (JV) curves of ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au and ITO / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au (labeled as: reference device). The graph shows that the performance of the perovskite photovoltaic device with the added BCP modification layer is significantly improved, with the device efficiency, short-circuit current density, open-circuit voltage, and fill factor increasing from 20.07% to 25.22 mA cm⁻¹. -2 The voltage and efficiency were improved from 1.093V and 72.28% to 22.03% and 25.72mA cm. -2 1.113V, 77.02%.

[0021] Figure 3 Cross-sectional scanning electron microscope (SEM) image of the ITO / BCP / SnO2 / perovskite structure, from... Figure 3 The growth of grains in each layer can be seen (the thickness of BCP in the figure is not marked because it is too thin). Figure 4The X-ray diffraction (XRD) patterns of the ITO / BCP / SnO2 / perovskite and ITO / SnO2 / perovskite structures are shown. After adding the BCP modification layer, the main peaks of the perovskite film are significantly enhanced, indicating that the optimized perovskite film has better crystallinity. Meanwhile, for the XRD curves of ITO / BCP / SnO2 / perovskite, it can be seen that the diffraction intensity of the (111) crystal plane is significantly stronger than that of the (100) crystal plane, indicating that the perovskite crystal orientation is optimized after adding the BCP modification layer, and the perovskite film with the (111) crystal plane orientation is beneficial for the fabrication of high-performance photovoltaic devices.

[0022] Figure 5 This is a stability comparison chart of two unencapsulated photovoltaic devices with ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au and ITO / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au structures. Figure 5 (a) shows the long-term stability of the two devices in a nitrogen environment. It can be seen that after 1200 hours of storage, the photoelectric conversion efficiency of the optimized device remains above 70% of its initial value, while the reference device only retains about 35% of its initial efficiency under the same test conditions. Figure 5 (b) shows the thermal stability test results of the two devices under nitrogen atmosphere and continuous heating at 85°C. It can be seen that after 630 hours of continuous heating, the photoelectric conversion efficiency of the optimized device remains at 77% of its initial value, while the reference device has degraded to about 30% of its initial value. Figure 5 (c) The two devices were continuously illuminated in a nitrogen atmosphere (illuminance of 100 mW cm⁻¹). -2 The photoelectric conversion efficiency of the optimized device remained at approximately 80% of its initial value after 475 hours of continuous illumination, while the reference device had degraded to approximately 40% of its initial value. The results clearly show that the photovoltaic device with the added BCP modification layer exhibited significantly improved room temperature stability, thermal stability, and photoelectric stability in a nitrogen atmosphere.

[0023] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions conceived without inventive effort should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.

Claims

1. A method for fabricating a perovskite photovoltaic device modified with BCP for photoelectrode, characterized in that, Includes the following steps: (1) Clean the ITO substrate and dry it with nitrogen, then treat the substrate with ultraviolet ozone; (2) Prepare and spin-coat BCP solution, and obtain ITO / BCP sample after ultraviolet ozone treatment; (3) Prepare SnO2 solution, spin-coat SnO2 solution on ITO / BCP substrate, and then obtain ITO / BCP / SnO2 sample after annealing and ultraviolet ozone treatment; (4) Prepare a PbI2 solution, spin-coat the PbI2 solution onto the sample obtained in step (3), and anneal it to obtain an ITO / BCP / SnO2 / PbI2 sample; (5) The ITO / BCP / SnO2 / PbI2 sample obtained in step (4) was spin-coated with a mixed solution of ammonium halide salts under nitrogen protection, and then annealed to obtain an ITO / BCP / SnO2 / perovskite sample. (6) Prepare PEAI solution and spin-coat PEAI solution onto the ITO / BCP / SnO2 / perovskite sample obtained in step (5) to obtain ITO / BCP / SnO2 / perovskite / PEAI sample; (7) Spin-coat spiro-OMeTAD onto the ITO / BCP / SnO2 / perovskite / PEAI sample obtained in step (6) to obtain the ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD sample; (8) Gold electrodes are deposited on the ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD sample obtained in step (7) to obtain a perovskite photovoltaic device with an ITO / BCP / SnO2 / perovskite / PEAI / spiro-OMeTAD / Au structure.

2. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (2), the preparation process of BCP solution is as follows: take BCP powder, add isopropanol, stir for 5-7 hours, and prepare a BCP solution of 0.5 mg / mL.

3. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (3), the SnO2 solution is prepared as follows: 15wt% SnO2 colloidal dispersion is diluted to 10wt% with deionized water and stirred evenly to obtain SnO2 solution.

4. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (4), the specific preparation process of PbI2 solution is as follows: PbI2 is dissolved in a mixed solution of DMF and DMSO with a volume ratio of 9:1 to obtain a 1.5 mol / L PbI2 solution.

5. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (5), the specific preparation process of the ammonium halide salt mixed solution is as follows: FAI, MAI, and MACl are added to isopropanol in a molar ratio of 52:4:13 to prepare an ammonium halide salt mixed solution, wherein the total concentration of FAI, MAI, and MACl in isopropanol is 105.36 mg / mL.

6. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (6), the preparation process of PEAI is as follows: PEAI is dissolved in isopropanol to prepare a 5 mg / mL PEAI solution.

7. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (7), the preparation process of spiro-OMeTAD is as follows: Take 72.5 mg of spiro-OMeTAD, add 1 ml of chlorobenzene, 18 μl of lithium bis(trifluoromethanesulfonyl)imide and 28.5 μl of 4-tert-butylpyridine, and stir for 10 to 15 hours.

8. The method for fabricating a perovskite photovoltaic device according to claim 1, characterized in that, In step (3), annealing means annealing at 100℃ for 5 minutes and then annealing at 150℃ for 10 minutes; in step (4), annealing means annealing at 70℃ for 1 minute; in step (5), annealing means annealing at 150℃ for 15 minutes in air with a humidity of 30%-40%.

9. The BCP prepared by any one of claims 1 to 8 is used in perovskite photovoltaic devices modified with photoelectrodes.

10. The perovskite photovoltaic device according to claim 9, characterized in that, The SnO2 layer is 40 nm thick, the perovskite layer is 650 nm thick, the spiro-OMeTAD layer is 160 nm thick, and the gold layer is 80 nm thick.

Citation Information

Patent Citations

  • Method for passivating lower interface of perovskite solar cell with inversion structure

    CN111092160A

  • Rapid vacuum gas phase deposition of perovskite thin film and preparation method of photovoltaic device of perovskite thin film

    CN116234400A